2017
DOI: 10.1155/2017/3780572
|View full text |Cite
|
Sign up to set email alerts
|

Are the Therapeutic Effects of Huangqi (Astragalus membranaceus) on Diabetic Nephropathy Correlated with Its Regulation of Macrophage iNOS Activity?

Abstract: Objective To investigate the correlation between the clinical effects of Huangqi (Astragalus membranaceus) on different stages of diabetic nephropathy (DN) and the pharmacological effect of Huangqi on the activity of inducible nitric oxide synthase (iNOS) in macrophages in different states. Methods The PubMed, China National Knowledge Infrastructure, and Wanfang databases were searched. Clinical data was sourced from papers on treatment of different stages of DN with Huangqi, and pharmacological data was from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…We has reported previously that EHF ameliorated renal damage in adenine-induced CRF rats, and the mechanisms might involve in the inhibition of inflammation and fibrotic responses (Zhang et al, 2017). The two main Chinese medicines comprising EHF, A. radix (Huangqi) and R. etrhizoma (Dahuang) have been reported for the treatment of DN (Xu et al, 2011;Liao et al, 2017). However, it is unclear whether EHF exerts an effect on DN.…”
Section: Introductionmentioning
confidence: 99%
“…We has reported previously that EHF ameliorated renal damage in adenine-induced CRF rats, and the mechanisms might involve in the inhibition of inflammation and fibrotic responses (Zhang et al, 2017). The two main Chinese medicines comprising EHF, A. radix (Huangqi) and R. etrhizoma (Dahuang) have been reported for the treatment of DN (Xu et al, 2011;Liao et al, 2017). However, it is unclear whether EHF exerts an effect on DN.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus membranaceus (AM) has a longstanding history and has gained widespread clinical applications in China, with the functions of lowering blood sugar, decreasing blood lipid, eliminating edema, antioxidative stress, and so on [5,6]. In addition, it has been proven to have wide pharmacological effects on diabetic diseases; particularly in DN aspects, it has a unique curative effect [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review preliminarily con rmed the therapeutic effect of AM injection on DN patients, such as reducing urinary protein and improving renal function (12). A pharmacological study had shown that AM could reduce proteinuria, reverse glomerular ltration and improve early or other stages of DN in streptozotocin induced diabetic animal models (13)(14)(15). The effect may be related to the effect of AM on TGF-β/ drosophila mothers against decapentaplegic protein (SMADs) signal pathway, down regulating the expression of TGF-β1, SMAD2/3, and delaying the process of renal brosis in diabetic mice (16).…”
Section: Introductionmentioning
confidence: 99%